2015
DOI: 10.1002/bab.1457
|View full text |Cite
|
Sign up to set email alerts
|

Efficient kinetic resolution of (±)‐menthol by a lipase from Thermomyces lanuginosus

Abstract: A lipase from Thermomyces lanuginosus (Lipozyme TL IM) exhibited high enantioselectivity for kinetic resolution of (±)-menthol in organic solvent. The various reaction parameters affecting the conversion and enantioselectivity were studied. The optimum reaction conditions for the transesterification reaction were found with vinyl acetate in the solvent of methyl tert-butyl ether with a vinyl acetate:(±)-menthol molar ratio of 5:1 and an enzyme concentration of 200 g/L at 30 °C. In these conditions, (-)-menthyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Thus, what we perceived as the most efficient approach was an enzymatic resolution. As shown, this idea worked with great facility following the generation of racemic 40 from 12 , using lipozyme 26 and the indicated acetate source to generate a separable mixture of (+)- 41 and (−)- 40 in near-perfect yield and ee . The undesired acetate could be smoothly recycled to 12 through ester hydrolysis, alcohol oxidation, and base-promoted nitrile expulsion.…”
mentioning
confidence: 99%
“…Thus, what we perceived as the most efficient approach was an enzymatic resolution. As shown, this idea worked with great facility following the generation of racemic 40 from 12 , using lipozyme 26 and the indicated acetate source to generate a separable mixture of (+)- 41 and (−)- 40 in near-perfect yield and ee . The undesired acetate could be smoothly recycled to 12 through ester hydrolysis, alcohol oxidation, and base-promoted nitrile expulsion.…”
mentioning
confidence: 99%
“…In this context, lipase from the fungus Candida rugosa exhibited high potential to resolve D,L-menthol in an organic solvent (Wang et al, 2002). Lipase from Thermomyces lanuginosus can perform high enantioselectivity for the kinetic resolution of (±)-menthol in organic solvent (De Yan et al, 2017).…”
Section: Lipolytic Enzymesmentioning
confidence: 99%
“…Out of the eight menthol stereoisomers, (−)-menthol ( 70) is the only enantiomer that can be used as flavor/fragrance. Since the racemic mixture of this alcohol is an affordable commodity secured by the chemical industry, a number of studies on its resolution have been reported, both in the academic and patent literature [53][54][55][56][57][58][59][60][61][62][63][64]. To this end, lipase from Candida rugosa (CRL LIP1), lipase PS, lipase from Candida cilindracea (CCL), lipase from Pseudomonas alcaligenes, lipase AK, and lipase from Thermomyces lanuginosus were successfully employed.…”
Section: Secondary Alcoholsmentioning
confidence: 99%